Immunologic Response and Clinical Course After Off-label Nonavalent HPV Vaccination in Juvenile-onset Recurrent Respiratory Papillomatosis Patients - Neele M. Thurau; Inga Tometten; Nadine Lübke; Birgitta E. Michels; Daniela Höfler; Fabian Rosing; Peter Sehr; Katharina Remke; Jörg Timm; Steffi Silling; Tim Waterboer; Dirk Schramm; et al. (Pediatric Infectious Disease Journal, 2026)
Background: Juvenile-onset recurrent respiratory papillomatosis (JoRRP) is a rare airway disease caused by human papillomavirus (HPV), most commonly HPV6 or HPV11. Affected children often require repeated surgical procedures, and no curative therapy exists. Off-label HPV vaccination has been proposed as an adjunctive treatment, but vaccine-induced immune responses and the relevance of circulating HPV DNA in benign disease remain unclear. Methods: We longitudinally evaluated 2 children with JoRRP who received off-label nonavalent HPV vaccination between 2020 and 2025. Serum HPV-specific binding and neutralizing antibodies were measured before vaccination and after the second and third doses using multiplex serology and a pseudovirion-based neutralization assay. During bronchoscopic follow-up, bronchoalveolar lavage fluid and available biopsy samples were analyzed for HPV DNA. In 1 patient, plasma was additionally tested for circulating HPV DNA by digital polymerase chain reaction. Results: Both children had low or undetectable HPV-specific antibodies at baseline. Vaccination induced strong binding and neutralizing antibody responses against vaccine-included HPV types. During post-vaccination follow-up of 12–29 months after completion of the vaccination series, HPV DNA became undetectable in bronchoalveolar lavage samples, and no new papilloma growth was observed after the last post-vaccination intervention. Circulating HPV DNA was not detected at any time point in the patient tested. Conclusions: Nonavalent HPV vaccination induced robust neutralizing antibody responses in children with JoRRP and was temporally associated with clinical stabilization. Larger studies are needed to clarify clinical benefit and biomarker utility.